The Boehm flute : its antecedents and its influence upon the repertoire - Mayer, Nerina von (College of Music, 2024)
This dissertation studies the physical evolution of the flute 1n conjunction with the development of the repertoire. A gulf, consisting of more than stylistic differences, appears to separate the flute music of the 20th and late 19th centuries from that of the Baroque and Classical periods. In the former, the furthest resources of the instrument are sensitively exploited by composers, while in the latter, a certain quality of constraint and distance is evident in its treatment of the flute. As compared to the modern repertoire, Baroque and Classical flute works might have been written for an entirely different instrument - as indeed they were. The flute as re-invented by Theobald Boehm is entirely different to the pre-Boehm instrument, possessing an extended range, technical facility, improved intonation and volume, and a sound both brilliant and flexible. The somewhat primitive and unsatisfactory pre-Boehm instrument imposed severe limitations on composers. However, with the Boehm flute came the flowering of a great repertoire and the foundation of a great school of flute playing. The rise of the flute from humble pastoral origins to the sophisticated modern concert instrument affords much interesting study. The dissertation will consist of examination of the physical developn1ent of the flute (with special reference to the work of Boehm), and of how this is reflected in the evolution of the repertoire, with investigation of the links between the French school of playing and much of the 20th century repertoire.